A qualitative inquiry of experiences of HIV-related stigma and its effects among people living with HIV on treatment in rural Kilifi, Kenya - Wanjala, Stanley W.; Nyongesa, Moses K.; Mapenzi, Rachael; Luchters, Stanley; Abubakar, Amina (Frontiers in Public Health, 2023)
Background: The pervasiveness of HIV-related stigma and discrimination, and its consequences on HIV prevention and treatment, have been well documented. However, little is known about the lived experiences of HIV-related stigma and its effects among the general adult population living with HIV in rural African settings. This study set out to explore this knowledge gap. Methods: From April to June 2018, we conducted in-depth interviews with a convenience sample of 40 adults living with HIV aged 18-60 years in Kilifi, Kenya. A semi-structured interview guide was used to explore experiences of HIV-related stigma and its impact on these adults. A framework approach was used to analyse the data using NVIVO 11 software. Results: Participants reported experiences of HIV-related stigma in its various forms (anticipated, perceived, internalized, and enacted), as well as its effects on HIV treatment and social and personal spheres. The internalisation of stigma caused by enacted stigma impacted care-seeking behaviour resulting in worse overall health. Anxiety and depression characterised by suicidal ideation were the results of internalised stigma. Anticipated stigma prompted HIV medication concealment, care-seeking in remote healthcare facilities, and care avoidance. Fewer social interactions and marital conflicts resulted from perceived stigma. Overall, HIV-related stigma resulted in partial and non-disclosure of HIV seropositivity and medication non-adherence. At a personal level, mental health issues and diminished sexual or marital prospects (for the unmarried) were reported. Conclusions: Despite high awareness of HIV and AIDS among the general population in Kenya, adults living with HIV in rural Kilifi still experience different forms of HIV-related stigma (including self-stigma) that result in a raft of social, personal, and HIV-treatment-related consequences. Our findings underscore the urgent need to reevaluate and adopt more effective strategies for implementing HIV-related anti-stigma programs at the community level. Addressing individual-level stigma will require the design of targeted interventions. To improve the lives of adults living with HIV in Kilifi, the effects of HIV-related stigma, particularly on HIV treatment, must be addressed.